Counterproductive work behaviours among police officers: the case for Police Headquarters of Bukit Aman, Kuala Lumpur / Hayyatul Atida Borhan - Borhan, Hayyatul Atida (2019)
Nowadays, as pointed out by Martinco, Gundlach and Douglas (2002), there has been an increase in the study as well as observation on the counterproductive work behaviours. Counterproductive work behaviours become a concern as it will give huge negative impacts to any organizations. Counterproductive work behaviours include all those violence, stealing, drugs, alcohol abuse, absenteeism as well as abuse of power and many other counterproductive work behaviours that had happened. Therefore, many observations have been given in order to explain the causes and effects of counterproductive behaviours that took place in the organization. In discussing the definition of counterproductive work behaviours, Collin and Griffin (1998) state that almost all the definitions of counterproductive behaviours at work defined as not respecting the rules and regulation as well as values of societies and organization. In addition, counterproductive work behaviours also known as or begin with making small mistakes such as stealing to make big mistakes such as violence and so on. Another definition shows that counterproductive work behaviours are an act that threatens the well-being of an organization and the members inside the organization which violates those implied rules and regulations (Baron & Richardson 1994~ Martinco & Zallar 1998~ Robinson & Bennet 1995). Thus, researchers agree that counterproductive work behaviours by the members of the organization can damage and bring bad image for the organization itself as well as to their members. It is undeniable that public service is a public sector which is very important for the development of a country. Apart from that, civil servants which also known as the government employees is one of the important sources to carry out any of government policy.